2017
DOI: 10.1107/s2059798317007446
|View full text |Cite
|
Sign up to set email alerts
|

The ribosome and its role in protein folding: looking through a magnifying glass

Abstract: Protein folding, a process that underpins cellular activity, begins cotranslationally on the ribosome. During translation, a newly synthesized polypeptide chain enters the ribosomal exit tunnel and actively interacts with the ribosome elements -the r-proteins and rRNA that line the tunnel -prior to emerging into the cellular milieu. While understanding of the structure and function of the ribosome has advanced significantly, little is known about the process of folding of the emerging nascent chain (NC). Advan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
32
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3
2

Relationship

2
7

Authors

Journals

citations
Cited by 36 publications
(33 citation statements)
references
References 139 publications
1
32
0
Order By: Relevance
“…Ribosomes are nano-machines that translate information coded in a messenger RNA into proteins in all living organisms. Recently, it has been found that ribosomes can also play a significant role in the process of co-translational folding by modulating the folding of a nascent chain (NC) during translation (Kaiser et al, 2011;Cabrita et al, 2016;Javed et al, 2017;Samulson et al, 2018;Liu et al, 2019). Nascent chains (NC) can begin to acquire secondary structural elements in a cotranslational manner during emergence via the ribosome exit tunnel within the large subunit of the ribosome (Netzer W. et al, 1997;Thommen et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Ribosomes are nano-machines that translate information coded in a messenger RNA into proteins in all living organisms. Recently, it has been found that ribosomes can also play a significant role in the process of co-translational folding by modulating the folding of a nascent chain (NC) during translation (Kaiser et al, 2011;Cabrita et al, 2016;Javed et al, 2017;Samulson et al, 2018;Liu et al, 2019). Nascent chains (NC) can begin to acquire secondary structural elements in a cotranslational manner during emergence via the ribosome exit tunnel within the large subunit of the ribosome (Netzer W. et al, 1997;Thommen et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…In the context of a diffusing particle inside the tunnel, we previously found [9] that this radial increase creates a strong entropic barrier, which can be compensated by the electrostatic potential if the particle is positively charged. More generally, it was also experimentally shown that electrostatics in the ribosomal tunnel modulate chain elongation rates [9,17] and can even induce ribosome stalling [46]. At the proteome-wide level, averaging the charged amino acid frequency over all translated genes in S. cerevisiae revealed an elevated (respectively, decreased) amount of positively (respectively, negatively) charged amino acids in the first āˆ¼ 20 codons [9].…”
Section: Impact On the Nascent Polypeptide Chain Transitmentioning
confidence: 95%
“…In addition to offering a mechanism to explain long-distance communication in fully translated proteins, our helix stabilization model might be relevant to co-translational folding. The ribosomal exit tunnel can accommodate [34][35][36][37] and stabilize helices 38 , but the potential role of these transient helices remains unclear. We posit that the stabilizing effect of the tunnel on these transient helices might be transmitted to the exposed nascent polypeptide chain, thereby stabilizing folding of the emerging N-terminus.…”
Section: Implications For Co-translational Foldingmentioning
confidence: 99%